Sterculia nobilis fiber composite material as well as preparation method and application thereof
By blending apple tree fibers with low melting point polypropylene and preparing composite materials using melt spinning and needle-punching processes, the problems of high energy consumption, difficult waste degradation and insufficient rigidity of existing automotive interior materials are solved, and efficient and environmentally friendly automotive interior materials are achieved.
Patent Information
- Application Number
- CN202411699623.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
AI Technical Summary
Existing automotive interior materials such as polypropylene (PP) have problems such as high energy consumption, difficult waste degradation, heavy parts, poor odor quality, high cost and insufficient rigidity, and cannot meet the growing requirements of carbon emissions, odority, weight loss and rigidity.
By extracting pineapple fibers and blending them with low melting point polypropylene, a composite material is prepared into a car interior part, and a composite material is crossed with the pineapple fiber mesh by melt spinning technology, and composite sheets are prepared through a needle puncture process.
The development of green and environmentally friendly materials has been achieved, carbon emissions have been reduced, odor performance has been improved, and the mechanical properties and sound absorption properties of composite materials have been improved, meeting the high rigidity, lightweight and environmental protection requirements of automotive interior parts.
Smart Images

Figure CN119704791A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of automobile interior materials, and particularly relates to a Sterculia sylvestris fiber composite material and a preparation method and application thereof. Background Art
[0002] The Sterculia styracifolia tree belongs to the family Sterculiaceae and is widely distributed in Guangxi. However, research and development on this tree is limited, with its main uses being fruit consumption and landscaping. However, due to its excellent bark fiber properties and high fiber content, it can be harvested on a large scale and in large quantities, offering significant economic value and development prospects.
[0003] Currently, most automotive interior parts are injection molded using polypropylene (PP). PP is made from non-renewable petroleum resources, resulting in high energy consumption and difficult waste degradation during production, hindering the country's carbon neutrality and carbon peak goals. PP also poses challenges such as heavy parts, poor odor, and high cost.
[0004] Chinese patent CN118085445A relates to a polypropylene composite material, a preparation method thereof, and an automotive component. By extruding and granulating polypropylene particles after adding plant fibers, the composite material is then injection molded into parts, thereby achieving excellent flame retardant properties, good health and environmental performance, and lightweight advantages. However, the proportion of plant fibers in the composite material is small, so it does not meet the growing demand in terms of carbon emissions, odor, and weight loss. At the same time, the product flexural modulus obtained by the patent is less than 3000Mpa, and the rigidity does not meet the requirements of today's thin-walled parts (the larger the flexural modulus, the better the rigidity, and the thinner the parts can be, thereby lightweighting). This may be due to the low proportion of plant fibers or factors such as the poor performance of the plant fibers themselves (for example, impurities in the plant fibers are not fully removed, affecting the performance of the fibers). In addition, when the composite material is prepared by the patent, additional additives such as flame retardants and antioxidants are added to ensure the performance of the parts, which causes an increase in material costs and is also unfavorable for VOC and odor. Finally, the patent is to perform injection molding on the composite material. The injection mold structure is complex and costly, and the stability of the parts obtained is also not good enough.
[0005] In view of this, the present invention designs a preparation method of a Sterculia sarmentosa fiber composite material and its application to solve the above problems. Summary of the Invention
[0006] This invention extracts Sterculia styracifolia fiber, then blends it with low-melting-point polypropylene (PP) fiber to create a composite material for automotive interior trim. In the automotive interior trim field, plant fiber composites often use hemp and bamboo fibers as reinforcement, but this is the first application of Sterculia styracifolia fiber. This invention effectively fills a gap in the application of Sterculia styracifolia fiber and effectively utilizes local resources in Guangxi.
[0007] A first aspect of the present invention provides a Sterculia sargentii fiber composite material, comprising Sterculia sargentii fiber and low-melting-point polypropylene, wherein the low-melting-point polypropylene is mixed with the Sterculia sargentii fiber by melt spinning.
[0008] According to the present invention, in the Sterculia sylvestris fiber composite material:
[0009] The melting point of the low-melting-point polypropylene is 140-170° C. For example, the melting point of the low-melting-point polypropylene can be 140, 145, 150, 155, 160, 165, 170° C. or a value between any two of the above numerical ranges; preferably, the melting point of the low-melting-point polypropylene is 150-160° C.;
[0010] The average length of the Sterculia sargentii fiber is 7 to 30 mm (for example, the average length of the Sterculia sargentii fiber may be 7, 8, 9, 10, 15, 20, 25, 30 mm or a value between any two numerical ranges above), and the diameter is 0.05 to 0.3 mm (for example, the diameter of the Sterculia sargentii fiber may be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3 mm or a value between any two numerical ranges above); preferably, the average length of the Sterculia sargentii fiber is 15 to 30 mm, and the diameter is 0.2 to 0.3 mm;
[0011] The breaking strength of a single fiber of the Sterculia sargentii tree fiber is 750-3500 MPa (for example, the breaking strength of a single fiber of the Sterculia sargentii tree fiber may be 750, 1000, 1500, 2000, 2500, 3000, 3500 MPa or a value between any two numerical ranges above), and the breaking elongation is 2-7% (for example, the breaking elongation of a single fiber of the Sterculia sargentii tree fiber may be 2, 3, 4, 5, 6, 7% or a value between any two numerical ranges above); preferably, the breaking strength of a single fiber of the Sterculia sargentii tree fiber is 2000-3200 MPa, and the breaking elongation is 5-7%;
[0012] The mass ratio of the Sterculia sylvestris fiber to the low-melting-point polypropylene is 4:6 to 6:4. Specifically, the mass ratio of the Sterculia sylvestris fiber to the low-melting-point polypropylene can be 4:6, 5:5, 6:4, or a value between any two of the above ratio ranges.
[0013] The second aspect of the present invention provides a method for preparing the above-mentioned Sterculia fiber composite material, including the step of melt-spinning low-melting-point polypropylene into a Sterculia fiber web to obtain a Sterculia fiber composite material. Preferably, the melt-spinning includes heating and melting the low-melting-point polypropylene in a screw extruder at 180 to 220°C, extruding it from the spinneret hole and blowing it out through 220 to 260°C hot air (the blower frequency is 20 to 30 Hz), and crossing it with the Sterculia fiber web to form a Sterculia fiber composite material.
[0014] According to the present invention, the preparation method of the Sterculia sargentii fiber web includes: cleaning the bark of the Sterculia sargentii, treating it with microwaves, peeling it off, immersing it in an alkaline treatment solution, taking it out and placing it in an acid treatment solution for acid neutralization, then placing it in an enzyme solution and letting it stand, and obtaining the Sterculia sargentii fiber web after cleaning, opening, combing, and laying the web.
[0015] According to the present invention, in the method for preparing the Sterculia sarmentosa fiber web:
[0016] The alkaline treatment solution comprises alkali metal hydroxide, urea and water; preferably, the alkali metal hydroxide is selected from at least one of sodium hydroxide and potassium hydroxide; in the alkaline treatment solution, based on 1 L of water, the alkali metal hydroxide is 12-15 g, and the urea is 26-30 g;
[0017] The acid in the acid treatment solution is selected from at least one of sulfuric acid and nitric acid. Preferably, the concentration of the acid in the acid treatment solution is 10-15 wt %;
[0018] The enzyme in the enzyme solution is selected from at least one of pectinase, xylanase, and hemicellulase. Preferably, the concentration of the enzyme in the enzyme solution is 1 to 3 g / L, and the pH of the enzyme solution is 5 to 9;
[0019] The microwave treatment conditions are as follows: microwave power 1-1.2 kW, microwave treatment time 1-3 min;
[0020] The conditions for immersing in the alkaline treatment solution are: temperature 20-40°C, time 12-48 hours; the immersion process of the alkaline treatment solution can be completed at room temperature;
[0021] The temperature of the acid neutralization is: 20-40°C; the acid neutralization can be completed at room temperature;
[0022] The enzyme solution is allowed to stand at a temperature of 40 to 60° C. for 1 to 4 hours.
[0023] According to a preferred embodiment of the present invention, the extraction of Sterculia sargentii fiber includes the following specific operation process: the bark of Sterculia sargentii is washed with a large amount of water to remove impurities and then placed in a microwave generator, and treated with a microwave power of 1 to 1.2 kW for 1 to 3 minutes. After peeling the bark of Sterculia sargentii, it is immersed in an alkaline treatment solution of alkali metal hydroxide / urea / pure water and magnetically stirred at room temperature for 12 to 48 hours. After the impregnation is completed, the bark of Sterculia sargentii is placed in a 10% to 15% acid solution for acid neutralization and magnetically stirred at room temperature. The bark is then placed in an enzyme solution (concentration 1 to 3 g / L, pH 5 to 9) and allowed to stand. After standing, the bark is taken out and washed with a large amount of water, and the Sterculia sargentii fiber is obtained after loosening and combing.
[0024] The average length of the Sterculia styracifolia fibers extracted by the present invention is 7-30 mm, and the diameter is 0.05-0.3 mm. Related research has shown that the breaking strength of fibers is strongly correlated with fiber length and aspect ratio, generally in a positive proportional relationship. The individual fibers extracted by the present invention have a breaking strength of 750-3500 MPa and an elongation at break of 2-7%. They exhibit superior performance and stable production consistency, making them an excellent reinforcement material.
[0025] The present invention pre-treats the Sterculia styraciflua bark through microwaves, thereby effectively reducing the combination of colloid and fiber and reducing the time for subsequent removal of Sterculia styraciflua pectin, hemicellulose and other impurities.
[0026] The treatment solution formulation ratio significantly impacts the extraction of Sterculia styracifolia fiber. In the treatment solution, the pectin, lignin, and hemicellulose in the Sterculia styracifolia fiber undergo alkaline degradation, resulting in weight loss. The addition of urea improves the extraction efficiency of Sterculia styracifolia fiber and improves the quality of the extracted fiber, increasing its softness and gloss.
[0027] Finally, the present invention extracts the Sterculia styracifolia fiber using an enzyme solution. Adding the Sterculia styracifolia bark to the enzyme solution under heated, alkaline conditions facilitates the extraction and release of plant cellulose. Furthermore, the mild enzyme treatment process avoids damage to the Sterculia styracifolia fiber structure, resulting in a purer, higher-quality extracted fiber.
[0028] A third aspect of the present invention provides a Sterculia sarmentosa fiber composite board, comprising a Sterculia sarmentosa fiber composite felt and polypropylene layers on both sides of the felt. The Sterculia sarmentosa fiber composite felt is made from the Sterculia sarmentosa fiber composite material.
[0029] The fourth aspect of the present invention provides a method for preparing the above-mentioned Sterculia fiber composite board, comprising: preparing Sterculia fiber composite material felt by a needle punching process using the Sterculia fiber composite material, then forming a polypropylene layer on both sides of the felt by a needle punching process, and obtaining the Sterculia fiber composite board after heating, cooling and pressing to shape it.
[0030] According to the present invention, in the method for preparing the Sterculia sarmentosa fiber composite board:
[0031] The thickness of the Sterculia sylvestris fiber composite felt is 8 to 20 mm, preferably 12 to 15 mm;
[0032] The surface density of the polypropylene layer is 40 to 120 g / m 2 , preferably 60 to 80 g / m 2 ;
[0033] The thickness of the polypropylene layer is 0.05 to 0.3 mm, preferably 0.05 to 0.1 mm;
[0034] The heating conditions are: temperature 160-230°C;
[0035] The shaping conditions of the press are: pressure 10-15 MPa, and holding time 10-30 s.
[0036] The performance of Sterculia fiber composite panels and products is not only related to the material properties of the Sterculia fiber itself, but also to the preparation of the composite material. The present invention melt-spins low-melting-point PP into a Sterculia fiber web and then needle-punches it. This improves the uniformity of the blend of Sterculia fiber and PP fiber, enhancing the mechanical properties of the composite material and avoiding the drawbacks of conventional lamination and molding processes, such as cumbersome processing and poor mechanical properties resulting from the delamination of the two materials.
[0037] The mixing ratio of Sterculia fiber and PP in this invention significantly influences product performance. Within a certain range, the performance of Sterculia fiber composites improves with adjustment of the Sterculia fiber ratio. In this invention, the Sterculia fiber to PP ratio that meets performance requirements is within a range of 4:6 to 6:4, with a 5:5 ratio being most preferred.
[0038] The present invention adds PP film layers on both sides of the felt material through a needle-punching process, and finally presses it into a Sterculia sylvestris fiber composite board. This can effectively prevent the back side of the bamboo fiber composite material used in the prior art from falling off and being punctured during processing, and is beneficial to transportation, packaging, manufacturing and processing.
[0039] A fifth aspect of the present invention provides a Sterculia sarmentosa fiber composite product, obtained by heat-softening the Sterculia sarmentosa fiber composite sheet and then compression-molding it. The conditions for heat-softening are: a heating temperature of 200-230°C for 3-7 minutes; and the conditions for compression-molding are: a pressure of 16-20 MPa for 30-50 seconds.
[0040] The heating temperature, heating time, and molding pressure significantly impact product performance. For example, heating temperatures below 200°C prevent the Sterculia sarmentosa fiber composite board from softening sufficiently, preventing product molding. Heating temperatures above 230°C can lead to carbonization of the Sterculia sarmentosa fiber, damaging the structure and impairing mechanical properties. Furthermore, increasing the heating time can lead to a darker product color, a burnt odor, and a decrease in perceived quality.
[0041] The present invention uses Sterculia styracifolia fiber composite materials to prepare automotive interior parts, which has the following advantages:
[0042] (1) Artemisia selengensis fiber composite material is a green and environmentally friendly material, which improves the problems of high energy consumption in the production process and difficult degradation of waste in traditional PP materials. Its carbon emissions are reduced by more than 30% compared with traditional PP materials.
[0043] (2) No chemical reagents are added during the preparation process of the Sterculia sarracenia fiber composite material. Compared with traditional PP injection molding materials, it has excellent odor performance and its VOC is much lower than that of traditional materials.
[0044] (3) The parts made of Sterculia sarracenia fiber composite materials are fiber-reinforced materials with the advantages of high modulus, high impact and high tensile strength. The mechanical properties of the parts are better than those of traditional PP injection molding materials. The bending modulus of the parts made of Sterculia sarracenia fiber composite materials is ≥3000MPa and the low-temperature notch impact is ≥4.5kJ / m 2 , tensile strength> 28MPa, much greater than the traditional PP injection molding material bending modulus> 1800MPa, low temperature notch impact> 3kJ / m 2 , tensile strength> 20MPa requirement;
[0045] (4) The parts made of Sterculia sarracenia fiber composite materials have low density and thin wall thickness, and the parts made of them are 15% to 30% lighter than those made of traditional PP injection molding materials;
[0046] (5) Since the fiber cross-section of the Sterculia sarracenia fiber composite material is covered with cavities of varying sizes, these cavities can absorb sound wave energy. Therefore, the parts made of this material have good sound absorption performance and can effectively reduce the noise inside the car. Its sound absorption coefficient is 0.3-0.55 and the sound insulation is 9.6-12.7dB, while the sound absorption coefficient of traditional PP injection molding materials is only 0.07-0.33 and the sound insulation is 5.98-6.37dB.
[0047] (6) The Sterculia sarmentosa fiber composite material has an excellent appearance and a soft touch. It has the appearance characteristics of natural plants. At the same time, it can be formed by needle punching the fabric on the composite material and then hot pressing to meet the requirements of the shape. At the same time, the process cost remains basically unchanged, and the production operation is convenient and simple.
[0048] (7) The flame retardant properties of Sterculia styracifolia fiber composites are excellent, with a burning rate of less than 32 mm / min, far below the national standard requirement of 100 mm / min;
[0049] (8) In the production process, the extraction process of raw materials of Sterculia sarmentosa fiber composites is simple, and the hot pressing molds of parts are simpler than injection molds, so the production is fast and the stability is high;
[0050] (9) The composite material of Sterculia styracifolia fiber is recyclable, and the scraps are easy to recycle and reuse, which has the conditions to achieve zero loss, can effectively reduce environmental pollution, and is in line with the environmental protection strategy of sustainable development;
[0051] (10) The Sterculia styracifolia tree is widely distributed in southern China and has certain industrial utilization value. The comprehensive cost of the Sterculia styracifolia fiber composite parts produced from it is 10% to 20% lower than that of traditional injection molded parts. After the scale effect is formed, the cost will be further reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a scanning electron microscope image of the Sterculia sylvestris fiber prepared in Example 1.
[0053] Figure 2 This is a scanning electron microscope image of the Sterculia sylvestris composite material obtained after melt spinning in Example 1.
[0054] Figure 3 This is the Sterculia sylvestris fiber composite board prepared in Example 1.
[0055] Figure 4 This is the Sterculia sylvestris fiber composite material part prepared in Example 1. DETAILED DESCRIPTION
[0056] The present invention will be described in detail below with reference to specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made by those skilled in the art to the present invention based on the contents of the present invention still fall within the scope of protection of the present invention.
[0057] The test standards used in the examples are as follows:
[0058] Flexural modulus: GB / T 9341
[0059] Breaking strength, breaking elongation: GB / T 1040.4
[0060] Low temperature notched impact: GB / T 1843
[0061] Sound absorption coefficient, sound insulation: GB / T 18696.2
[0062] Burning rate: GB 8410.
[0063] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0064] Example 1
[0065] Extraction of Sterculia sarmentosa fiber:
[0066] After washing the bark of the Sterculia styraciflua with a large amount of water to remove impurities, it is placed in a microwave generator and treated with a microwave power of 1kW for 2 minutes. The bark of the Sterculia styraciflua is peeled manually, 500g is weighed and immersed in an alkaline treatment solution of sodium hydroxide / urea / purified water, and magnetically stirred at room temperature for 24 hours. Among them, the alkaline treatment solution contains 15g of sodium hydroxide, 28g of urea, and 1L of deionized water. After the immersion is completed, the Sterculia styraciflua bark is placed in a 12% sulfuric acid solution for acid neutralization and magnetically stirred at room temperature for 2 hours. The bark is then placed in a pectinase solution (concentration 2g / L, pH=9) and allowed to stand at 50°C for 2 hours. After standing, the bark is taken out and washed with a large amount of water, and the Sterculia styraciflua fiber is obtained after being loosened and combed. The average length of the obtained Sterculia styraciflua fiber is 25mm and the average diameter is 0.3mm; the breaking strength of a single Sterculia styraciflua fiber is 3136MPa and the elongation at break is 7%.
[0067] Preparation of Sterculia sarmentosa fiber composite board:
[0068] The sterculia fiber was opened, carded, and laid, and low-melting-point PP (melting point 150°C, Kingfa Technology Co., Ltd.) was heated and melted at 200°C in a screw extruder, extruded from the spinneret hole, and then blown out at high speed by 240°C hot air (blower frequency was 25Hz) into the fiber web to obtain a sterculia fiber composite material, wherein the mass ratio of sterculia fiber to polypropylene was 5:5; then a composite felt material was made by a needle-punching process, and then a PP film layer (surface density 70g / m2) was added to the front and back sides of the felt material by a needle-punching process. 2 The composite felt was heated to 180° C. and then pressed in a cooling press at 12 MPa for 20 seconds to form a Sterculia sylvestris fiber composite board.
[0069] Preparation of Sterculia sarmentosa fiber composite parts:
[0070] The Sterculia sarracenia fiber composite sheet was softened by heating at 220°C for 5 minutes. It was then immediately placed in a mold for press molding to produce a Sterculia sarracenia fiber composite part. The mold pressure was set at 20 MPa and the hold time was 50 seconds. The performance test results of the Sterculia sarracenia fiber composite part are shown in Table 1.
[0071] Example 2
[0072] The preparation process of Example 1 was followed, except that different preparation conditions were used to extract the Sterculia styracifolia fiber, specifically:
[0073] After the bark of the Sterculia cuneiformis is peeled manually, 500g is weighed and immersed in an alkaline treatment solution of sodium hydroxide / urea / pure water, and magnetically stirred at room temperature for 24 hours. Among them, the alkaline treatment solution contains 12g sodium hydroxide, 26g urea, and 1L deionized water. After the impregnation is completed, the Sterculia cuneiformis bark is placed in a 12% sulfuric acid solution for acid neutralization, and magnetically stirred at room temperature for 2 hours. The bark is then placed in a pectinase solution (concentration 1g / L, pH=5) and allowed to stand at 90°C for 2 hours. After standing, the bark is taken out and washed with a large amount of water, and the Sterculia cuneiformis fiber is obtained after loosening and combing. The average length of the obtained Sterculia cuneiformis fiber is 15mm and the diameter is 0.2mm; the breaking strength of a single Sterculia cuneiformis fiber is 2876MPa, and the elongation at break is 6%.
[0074] The performance test results of the Sterculia sylvestris fiber composite parts are shown in Table 1.
[0075] Example 3
[0076] The preparation process of Example 1 was followed, except that different preparation conditions were used to prepare the Sterculia styracifolia fiber composite material, specifically:
[0077] The Sterculia sarcocarpa fiber was opened, carded, and laid, and low-melting-point PP (150°C, Kingfa Technology Co., Ltd.) was heated and melted at 180°C in a screw extruder, extruded from the spinneret hole, and then blown out at high speed by 220°C hot air (the blower frequency was 20Hz) into the fiber web to obtain a Sterculia sarcocarpa fiber composite material, wherein the mass ratio of Sterculia sarcocarpa fiber to polypropylene was 4:6; then a composite felt material was made by a needle punching process, and then a PP film layer (surface density of 60g / m2) was added to the front and back sides of the felt material by a needle punching process. 2 The composite felt was heated to 160° C. and then pressed in a cooling press at 10 MPa for 10 seconds to form a Sterculia sylvestris fiber composite board.
[0078] The performance test results of the Sterculia sylvestris fiber composite parts are shown in Table 1.
[0079] Example 4
[0080] The preparation process of Example 1 was followed, except that different preparation conditions were used to prepare the Sterculia styracifolia fiber composite material, specifically:
[0081] The Sterculia sarcocarpa fiber was opened, carded, and laid, and low-melting-point PP (150°C, Kingfa Technology Co., Ltd.) was heated and melted at 180°C in a screw extruder, extruded from the spinneret hole, and then blown out at high speed by 220°C hot air (the blower frequency was 20Hz) into the fiber web to obtain a Sterculia sarcocarpa fiber composite material, wherein the mass ratio of Sterculia sarcocarpa fiber to polypropylene was 6:4; then a composite felt material was made by a needle punching process, and then a PP film layer (surface density of 60g / m2) was added to the front and back sides of the felt material by a needle punching process. 2 The composite felt was heated to 160° C. and then pressed in a cooling press at 10 MPa for 10 seconds to form a Sterculia sylvestris fiber composite board.
[0082] The performance test results of the Sterculia sylvestris fiber composite parts are shown in Table 1.
[0083] Example 5
[0084] The preparation process of Example 1 is the same, except that different preparation conditions are used to prepare the Sterculia sarmentosa fiber composite board, specifically:
[0085] The Sterculia sarracenia fiber composite sheet was softened by heating at 230°C for 7 minutes and then immediately placed in a mold for compression molding to produce a Sterculia sarracenia fiber composite part. The compression pressure was set at 19 MPa and the holding time was 30 seconds.
[0086] The performance test results of the Sterculia sylvestris fiber composite parts are shown in Table 1.
[0087] Comparative Example 1
[0088] Low-melting-point PP fiber and Sterculia sylvestris fiber (same as in Example 1) were mixed in a 5:5 mass ratio and then processed through opening, carding, web laying, and needle punching to produce a Sterculia sylvestris fiber felt (8 mm thick). The Sterculia sylvestris fiber composite felt was then softened by heating at 220°C for 5 minutes. The final part was then formed by pressing at 20 MPa for 30 seconds to form the felt. The performance test results of the Sterculia sylvestris fiber composite parts are shown in Table 1.
[0089] Comparative Example 2
[0090] The PP injection molding particles were fed into the injection molding machine and injection molded at a mold temperature of 210°C. The performance test results of the products are shown in Table 1.
[0091] Table 1
[0092]
[0093] It can be seen from the test results in Table 1 that compared with the polypropylene injection molded parts in Comparative Example 2, the flexural modulus of the Sterculia sargentii fiber composite parts obtained in Examples 1 to 4 increased from 1700 MPa to more than 3000 MPa. However, when the proportion of Sterculia sargentii fiber exceeds 50%, the internal adhesion of the composite material decreases due to the reduction of PP fiber, and the bending performance is reduced. Moreover, the flexural modulus of the Sterculia sargentii fiber composite parts is ≥3000 MPa, and the low-temperature notched impact is ≥4.5 kJ / m 2 , tensile strength> 28MPa, much greater than the traditional PP injection molding material bending modulus> 1800MPa, low temperature notch impact> 3kJ / m 2 , tensile strength > 20MPa requirements; its sound absorption coefficient is 0.3~0.55, and the sound insulation volume is 9.6~12.7dB, while the sound absorption coefficient of traditional PP injection molding materials is only 0.07~0.33, and the sound insulation volume is 5.98~6.37dB.
[0094] Compared with Comparative Example 1, the product prepared by melt-spinning low-melting-point PP into a fiber web in Example 1 of the present application has more excellent mechanical properties and better sound absorption effect.
Claims
1. A Sterculia sargentii fiber composite material, comprising Sterculia sargentii fiber and low melting point polypropylene, wherein the low melting point polypropylene is mixed with the Sterculia sargentii fiber by melt spinning.
2. The Sterculia sarmentosa fiber composite material according to claim 1, characterized in that: The melting point of the low melting point polypropylene is 140 to 170° C., preferably 150 to 160° C.; and / or, The average length of the Sterculia sargentii fiber is 7-30 mm, and the diameter is 0.05-0.3 mm; preferably, the average length of the Sterculia sargentii fiber is 15-30 mm, and the diameter is 0.2-0.3 mm; and / or, The breaking strength of a single fiber of the Sterculia sargentii fiber is 750-3500 MPa, and the breaking elongation is 2-7%; preferably, the breaking strength of a single fiber of the Sterculia sargentii fiber is 2000-3200 MPa, and the breaking elongation is 5-7%; and / or, The mass ratio of the Sterculia oxyphylla fiber to the low-melting-point polypropylene is 4:6 to 6:
4.
3. A method for preparing the Sterculia fiber composite material according to any one of claims 1 to 2, comprising the step of melt-spinning low-melting-point polypropylene into a Sterculia fiber web to obtain the Sterculia fiber composite material. Preferably, the melt-spinning comprises heating and melting the low-melting-point polypropylene at 180 to 220°C in a screw extruder, extruding it from the spinneret hole and blowing it out through hot air at 220 to 260°C to cross with the Sterculia fiber web to form the Sterculia fiber composite material.
4. The preparation method according to claim 3, characterized in that: The preparation method of the Sterculia sargentii fiber web comprises: washing the bark of the Sterculia sargentii, subjecting it to microwave treatment and then peeling it off, then immersing it in an alkali treatment solution, taking it out and placing it in an acid treatment solution for acid neutralization, then placing it in an enzyme solution for standing, and obtaining the Sterculia sargentii fiber web after washing, loosening, combing and web laying.
5. The preparation method according to claim 4, characterized in that: The alkaline treatment liquid comprises alkali metal hydroxide, urea and water; preferably, the alkali metal hydroxide is selected from at least one of sodium hydroxide and potassium hydroxide; and / or, in the alkaline treatment liquid, based on 1L of water, the alkali metal hydroxide is 12-15g, and the urea is 26-30g; and / or, The acid in the acid treatment solution is selected from at least one of sulfuric acid and nitric acid. Preferably, the concentration of the acid in the acid treatment solution is 10-15 wt %; and / or, The enzyme in the enzyme solution is selected from at least one of pectinase, xylanase and hemicellulase. Preferably, the concentration of the enzyme in the enzyme solution is 1-3 g / L, and / or the pH of the enzyme solution is 5-9.
6. The preparation method according to claim 4, characterized in that: The microwave treatment conditions are: microwave power 1-1.2 kW, microwave treatment time 1-3 min; and / or, The conditions for immersion in the alkaline treatment solution are: temperature 20-40° C., time 12-48 h; and / or, The acid neutralization temperature is: 20-40°C; and / or, The enzyme solution is allowed to stand for 1 to 4 hours at a temperature of 40 to 60°C.
7. A Sterculia sargentii fiber composite board material, comprising a Sterculia sargentii fiber composite material felt material and polypropylene layers on both sides of the felt material, wherein the Sterculia sargentii fiber composite material felt material is made from the Sterculia sargentii fiber composite material described in any one of claims 1 to 2 or the Sterculia sargentii fiber composite material obtained by the preparation method described in any one of claims 3 to 6.
8. A method for preparing the Sterculia sarmentosa fiber composite board according to claim 7, comprising: The Sterculia fiber composite material is prepared into a Sterculia fiber composite material felt material through a needle punching process, and then a polypropylene layer is formed on both sides of the felt material through a needle punching process. After heating and cooling the press to shape, the Sterculia fiber composite board is obtained.
9. The preparation method according to claim 8, characterized in that: The thickness of the Sterculia sarmentosa fiber composite felt material is 8 to 20 mm, preferably 12 to 15 mm; and / or, The surface density of the polypropylene layer is 40 to 120 g / m 2 , preferably 60 to 80 g / m 2 and / or, The thickness of the polypropylene layer is 0.05 to 0.3 mm, preferably 0.05 to 0.1 mm; and / or, The heating conditions are: temperature 160-230° C.; and / or, The conditions for the press molding are: pressure 10-15 MPa, and pressure holding time 10-30 s.
10. A Sterculia sarmentosa fiber composite product, obtained by heating and softening the Sterculia sarmentosa fiber composite board according to claim 7 or the Sterculia sarmentosa fiber composite board obtained by the preparation method according to any one of claims 8 to 9 and then compression molding.
11. The composite material product made of Sterculia sarmentosa fiber according to claim 10, characterized in that: The conditions for heating and softening are: heating temperature 200-230° C., heating time 3-7 min; and / or, The compression molding conditions are: a pressure of 16 to 20 MPa and a holding time of 30 to 50 seconds.
Citation Information
Patent Citations
Polypropylene composite material, preparation method thereof and automobile part
CN118085445A
Automobile inner decorative board made of composite materials of natural fibers / thermoplastic resin, and mixing method of composite materials of natural fiber / thermoplastic resin
CN103481838A
Fiber reinforcement polymer felt material and composite board with polypropylene knitting surface course
CN206765469U
Compound melt blow sheet and its manufacture and filter unit
JP1995076053A
Natural Fiber reinforced composite board for vehicle headliner of multi-layers structure using thermoplastic matrix fibers of high crystalline and bonding to improve heat resistance and streng ...
KR101279522B1